Available Copper, Zinc, Manganese and Iron Status of Rajasthan Soils - Mehra, R K; Baser, B L (Annals of Arid Zone, 2016)
Soil samples representing Pellusterts, Chromusterts. Haplustalfs and Ustochrepts great groups of Rajasthan were collected and investigated for available content of micronutrient elements. Available (DTPA extractable) copper, zinc, manganese and iron were found to range between 0.18 ppm to 7.40 ppm, 0.20 ppm to 1.80 ppm,2.05 ppm to 12.00 ppm and 1.5 ppm to 11.28 ppm respectively. Soils were adequate in available copper content, but deficient in available zinc followed by manganese and iron. Positive significant correlations were found between organic matter and available copper, zinc, manganese and iron. Available manganese and iron decreased significantly with calcium carbonate in some of the soil great groups under study. Available manganese decreased significantly with increase in pH only in Ustochrepts.